Q: What is the answer to (2a plus 3)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

9a +8 -2a -3 -5a = 2a +5

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

2a-3+4b-2a-b-3+5=3b-1

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

-4 + 10 + 6a - 2a + 3 9 + 4a

3b -1

9a +8 -2a -3 -5a = 2a +5

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

2a+5a=3 7a=3 a=3/7 or .4286

7a-3

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1